Pendampingan dan penyuluhan imunisasi dasar lengkap - Niar, Niar; Hasriani, Hasriani (Yayasan Inspirasi El Burhani, 2024)
Introduction: Immunization is the most effective and efficient public health effort in preventing several dangerous diseases. The large role of immunization in saving the world community from pain, disability, and even death due to diseases that can be prevented by immunization such as Smallpox, Polio, Tuberculosis, Hepatitis B, Diphtheria, Measles, Rubella, Tetanus, Pneumonia, Meningitis, and encephalitis. Objective: to increase parents' knowledge through mentoring and counseling about the importance of complete basic immunization for babies at Posyandu Mekar Jaya Batu-batu environment, Darma sub-district. Method: Community service activities carried out include assistance and education regarding complete basic immunization for children. The media used is leaflet material.Implementation of community service uses the community outreach method, namely involving the community and students during the implementation process Result: From the results of the pre-test analysis, most mothers did not know about the importance of stimulation, early intervention detection and growth and development, but after counseling, the post-test results showed that almost all mothers understood the importance of complete basic immunization. Conclusion: From the community service activities that have been carried out at Posyandu Mekar Jaya in the Batu-Batu neighborhood, Darma Village by the community service team of STIKES Bina Generasi Polewali Mandar, it can be concluded that complete basic immunization assistance and counseling activities have been carried out for children and this activity has received a positive response. From partners, it can be seen that during counseling there is quite intensive communication interaction and increased knowledge and high awareness of carrying out complete basic immunization for their children through posyandu/puskesmas. Community service activities can be used as a reference or reference for respondents' knowledge about complete basic immunization for children